Stress echocardiography in the diagnosis of coronary artery disease: A systematic review - Castro Filho, Jorge João dos S.; Neufeld, Paulo M. (Brazilian Journal of Health and Biomedical Sciences, 2021)
Introduction: Coronary Artery Disease (CAD) contributes to the increase in the prevalence of cardiovascular disease, being the main cause of death worldwide. Objectives: This study compares the sensitivity of different methods of execution of Stress Echocardiography (SE) as to the accuracy in determining the presence of CAD, through a Systematic Literature Review (RSL). Methods: The databases of the Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (Lilacs) and the Spanish Bibliographic Index of Health Sciences (IBECS) were searched through the Virtual Health Library (VHL) for articles published until December 2018 and including scientific articles published in journals, in any language, which met the following criteria: (A) Descriptive or analytical studies of primary or secondary basis and (B) Studies whose theme was the SE in adult coronary heart disease. Studies related to: (a) Elderly; (b) Animals; (c) Children and Adolescents; (d) Pregnant women; (e) Articles that alluded to left ventricular function, valvulopathies, aneurysms, endocarditis, arrhythmias, implanted electronic devices and other titles that were outside the scope of this work and (f) Articles published in languages other than English or Neolatin languages. Results: The study has selected 14 articles, which demonstrated that SE was accurate to diagnose CAD with sensitivities ranging from 41 to 100% with studies included within the normality curve, demonstrating that it is an excellent tool for the diagnosis of CAD compared to other methods.